COMPARISON OF HOSPITAL MARKETING TEAM KNOWLEDGE BEFORE AND AFTER ATTENDING CUSTOMER RELATIONSHIP MANAGEMENT (CRM) TRAINING - Noor, Hesty Latifa; Yuliani, Novita; Nugraini, Alifah Sari (LPPM Universitas Duta Bangsa Surakarta, 2023)
PKU Muhammadiyah Sukoharjo Hospital is a type C hospital in Sukoharjo Regency. Currently, the marketing team at PKU Muhammadiyah Sukoharjo Hospital is starting to pioneer the development of marketing efforts which are expected to increase patient visits. Problems that exist in terms of marketing include patient visits still tend to fluctuate, there are still few visitors on the YouTube channel and visitors on Instagram social media are still low. High competition between hospitals is one of the factors that patient visits at PKU Muhammadiyah Sukoharjo Hospital tend to fluctuate. The marketing team's lack of knowledge regarding marketing strategies and the large number of marketing members who have double jobs result in less than optimal marketing efforts. This research carried out an intervention to measure the marketing team's knowledge before and after carrying out training related to Customer Relationship Management (CRM). Customer Relationship Management (CRM) is a business strategy that combines processes, people and technology. The research was carried out in August 2023 at the PKU Muhammadiyah Sukoharjo Hospital. The subjects in this research were 16 people from the Hospital marketing team consisting of Marketing, Public Relations and IT. The median score from the knowledge pre-test was 30, while the score median of post-test knowledge is 80. Bivariate analysis results p=0.000. There are significant differences between cadre knowledge before and after training.